Examining distributed leadership in Saudi Arabia, through the lens of sociocultural theory: case studies of public and private girls’ primary schools in Jeddah and AlMadinah - AlFahal, Soha (2022)
There is limited literature on school leadership in the Arab region and, particularly, in Saudi Arabia. It is even more limited in respect of leadership practices in primary schools. This study is significant as it contributes to the research on school leadership in Saudi Arabia and serves to modify established theory on distributed leadership. This study focuses on examining Distributed Leadership in Saudi Arabia, through the lens of Sociocultural Theory: Case studies of public and private girls’ primary schools in Jeddah and AlMadinah. It employs a multiple case study design of public and private schools in two cities in the Western region of Saudi Arabia. It sought to build an understanding of the enactment of leadership in the case study schools by exploring the applied leadership models and styles, in particular the distributed leadership model. It also investigates the elements affecting school leadership in Saudi Arabia through the lens of sociocultural theory. The findings show that there is evidence of leadership distribution in the case study schools. However, the nature and extent of distribution differs between the public and private schools, and the impact of centralisation, via the Ministry of Education, seems to constrain the level of distribution. The enactment of school leadership appears to be affected and influenced by the surrounding context; which is influenced by sociocultural factors, such as gendered roles and societal expectations.